Dinamika interaksi sosial dalam program literasi di ruang kelas Bahasa Indonesia: Studi pada Sekolah Negeri Kota Bandar Lampung - Hasanah, Uswatun (Universitas Lampung, 2024)
This research aims to determine the dynamics of social interaction in literacy programs in classrooms. This research uses qualitative research, with a descriptive approach, which aims to describe the literacy program at SD Negeri 1 Sukarame Dua. Data collection techniques use observation. Interviews, documentation, and triangulation or combination. The results of research in the literacy program at Sukarame Dua State School 1 show that social interactions between teachers and students, as well as between students and each other, have a significant influence on literacy development. Positive and rich social interactions can build enthusiasm for learning, facilitate the exchange of ideas and knowledge, and encourage collaboration between students. However, challenges such as students' lack of interest in reading, lack of adequate social interaction, and limited resources such as limited reading materials, can affect students' ability to communicate and understand reading materials well. Therefore, efforts are needed to increase students' interest in reading, improve social interactions between students and teachers, and expand resources such as reading materials and learning facilities in order to run optimal literacy programs. Keywords: Social Interaction, Literacy Program, School